P1 Quality of life related to COPD and occupational exposures. (16th November 2010) - Darby, AC; Waterhouse, JC; Stevens, V; Billings, CG; Hickman, SE; Seriki, A; Wight, J; Fishwick, D
Abstract : Introduction: COPD is associated with a considerable degree of morbidity and mortality and has been shown to adversely affect quality of life. One of the aims of a large epidemiological study of COPD and occupation in Sheffield was to evaluate quality of life. Having previously presented data from our initial survey using the EQ-5D tool and self-reported COPD1, we now present data from the follow up phase of the population based study using the more detailed quality of life estimate SF-36v2 and COPD defined by spirometry. Methods: A random population sample of 4000 Sheffield residents aged over 55 years was approached for study in 2007, along with a supplemental sample of 209 people with likely COPD recruited from a hospital physiology department. A detailed questionnaire recorded demographics, respiratory symptoms and diagnoses, smoking and occupational exposures. A proportion were re-visited in 2009–2010 for further spirometry and quality of life measure using the SF-36v2, which consists of 36 questions, divided into 8 domains, scores being converted to a scale from 0 to 100, the higher score indicating better health. Results: 549 people participated in the follow up phase, of whom 361 completed the SF-36v2. Abstract P1 Figure 1 shows mean scores for each of four different categories relating to COPD (defined by GOLD level 1 spirometry) and ever exposure to vapours, gases, dust and fumes (VGDF) in the workplace. In all domains, the group with airways obstruction has lower mean values than those without, and those who also report exposure to VDGF at work have further reductions (p<0.05). Of the 103 people in this group who have airways obstruction, those who also self-report a diagnosis of COPD (n=49) have significantly worse (p<0.05) quality of life than those who have no self-reported diagnosis. Conclusions: Those with GOLD 1 or greater COPD have an adverse quality of life as compared to those without airways obstruction, differences in scores being greater for the physical rather than emotional domains. Occupational exposure to VGDF also appears to adversely affect quality of life estimates.